2020
DOI: 10.3390/en13215588
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price, Energy Consumption, and CO2 Emissions in Turkey. New Evidence from a Bootstrap ARDL Test

Abstract: The main objective of this research was to test the effect of oil prices, renewable and non-renewable energy consumption, and economic growth on Turkey’s carbon emissions by using three co-integration tests, namely, the newly-developed bootstrap autoregressive distributed lag (ARDL) testing technique as proposed by (McNown et al., 2018); the new approach involving the Bayer–Hanck (2013) combined co-integration test; and the H-J (2008) co-integration technique, which induces two dates of structural breaks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 44 publications
3
21
0
1
Order By: Relevance
“…Bento and the authors of [17] tested the influence of fossil fuels consumption and economic growth on CO 2 emissions in Italy over the tested period from 1960-2011, the outcomes found that fossil fuels energy and GDP positively affect CO 2 emissions, and suggested that nonrenewable energy consumption has an inverse relation with carbon emission. The authors of [18] used the ARDL approach, and examined the validity of the EKC in Turkey. The findings affirmed that an increase in real GDP and energy consumption increased carbon emissions for this country.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…Bento and the authors of [17] tested the influence of fossil fuels consumption and economic growth on CO 2 emissions in Italy over the tested period from 1960-2011, the outcomes found that fossil fuels energy and GDP positively affect CO 2 emissions, and suggested that nonrenewable energy consumption has an inverse relation with carbon emission. The authors of [18] used the ARDL approach, and examined the validity of the EKC in Turkey. The findings affirmed that an increase in real GDP and energy consumption increased carbon emissions for this country.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…The most prominent global environmental agreements are the Kyoto Protocol (1997) and the Paris agreement (2015). These agreements strongly recommend energy efficiency improvements and green energy sources as optimal solutions to reduce the amount of carbon dioxide [1]. By complying with global environmental agreements, several developed and developing countries have considered sources of renewable energy as alternative green energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple regression for the nonstationary data may generate a spurious regression that leads to unreliable results. Autoregressive and distributed lag (ARDL) takes into account sufficient lags of variables to avoid nonstationarity [25][26][27]. The Durbin-Watson test is used to verify the reliability of the analysis.…”
Section: Top-down Econometric-based Demand Modelmentioning
confidence: 99%